Occult Cancer in Patients with Venous Thromboembolism: which Patients, which Cancers - Monreal, Manuel; Fernandez-Llamazares, Jaume; Perandreu, Joan; Urrutia, Agustin; Sahuquillo, Joan Carles; Contel, Elena (Thrombosis and Haemostasis, 1997)
We have previously demonstrated that patients with idiopathic venous thromboembolism (VTE) have a higher frequency of underlying cancer. Now we present a retrospective analysis of our 5-year experience with a series of 674 consecutive otherwise healthy patients, and a more restricted battery of diagnostic tests. Occult cancer was found in 15 patients during admission. The diagnostic tools which led to suspect occult cancer were: abdominal CT-scan (4 patients); high carcinoembryonic levels (2 patients); and high prostate-specific antigen levels (9 patients). Eight further patients were diagnosed of cancer after discharge. Cancer was more commonly found in patients with idiopathic VTE: 13/105 patients (12%) versus 10/569 patients (2%); p <0.01; 0. R.: 7.9 (95% Cl: 3.14-20.09).During the same period of time we diagnosed VTE in 147 patients with previously known cancer. When overall considered, VTE was the first sign of malignancy in most patients with prostatic and pancreatic carcinoma. On the contrary, most patients with breast, lung, uterine and brain cancers developed VTE as a terminal event of the disease. At variance with VTE patients and previously known cancer, most patients with occult malignancy were at an early stage. Further studies are needed to confirm whether patients with idiopathic VTE could benefit from screening for occult cancer. Meanwhile, our findings may serve as guidelines for physicians in this field.